“Little Science” vs “Big Science” no norte do Brasil: um estudo sobre a evolução acadêmica dos Institutos Federais Amazônicos - CARDOSO, Suzana (2021)
This study aims to investigate the main characteristics of the scientific production of the Federal Institutes (FIs) of the Northern Region in their evolution towards the "Big Science", or "Mainstream" science, in order to visualize their performance in knowledge production and human capital, in the context of the difficulties of an academically and economically peripheral region. It aims to examine, specifically, from the concepts of Big Science, Center-Periphery and the types of Capital, the scientific evolution of the FIs in Northern Brazil; to contextualize the historical facts of the FIs and socioeconomic facts of the Region, which sustain its condition of academic periphery in the Brazilian global and national system; to identify and analyze indicators of scientific production for evaluation of scientific performance and its potential to contribute to the sustainable development of the region. The research is characterized as a case study, using bibliometric and scientometric indicators and economic data. In scientific capital, 890 articles and 2,758 citations were retrieved from the period 2009 to 2019. The results indicated a cumulative linear growth of 46% over the analyzed period. The most prevalent language was English, with 70.1% in publications. A balanced trend of publications in national and international journals was noted (51.5% versus 48.5%, respectively). The impact of the journals was ranked as high impact (Q1=21%), medium impact (Q2=21%), low impact (Q3=21% and Q4=17%) and no ranking 20%. In social capital, regional collaboration had the highest occurrence with institutions in the North Region and Southeast Region, and internationally with the United States. In intellectual capital, the Northern FIs presented the lowest qualification index in relation to the Southeastern FIs (5.2% against 36.3%). In economic capital, the data indicated that the Northern FIs and their region received the lowest investments for education, for research, and for S&T. It was concluded that low investments (dominant capital) prevent FIs from reaching a level of scientific maturity capable of driving the transition from local to global science.